Plasma Kallikrein-Kinin System in Patients with Uncomplicated Sepsis and Septic Shock-Comparison with Cardiogenic Shock - Martínez-Brotóns, F; Oncins, J R; Mestres, J; Amargós, V; Reynaldo, C (Thrombosis and Haemostasis, 1987)
Alterations of the kallikrein-kinin system consistent with activation and increased consumption have been re2ported in septic patients and it has been suggested that this activation could contribute to the development of septic shock.The aim of this work was to confirm these alterations in septic patients and to investigate the possible existence of similar changes in subjects developing cardiogenic shock secondary to myocardial infarction as a model of non septic shock.Patients with septic shock, especially in fatal cases, showed a highly significant decrease in levels of factor XII, prekallikrein, high molecular weight kininogen (HMW-kininogen), α2-macro-globulin (α2-M) and antithrombin III (AT-III). C1-esterase inhibitor (C1-INH) activity was increased in uncomplicated sepsis but came back to normal or was slightly decreased in septic shock.Components and inhibitors of the kallikrein-kinin system were within normal limits in patients with cardiogenic shock.Our findings support the idea of a contribution of the kallikrein-kinin system to the development of septic shock though this system does not seem to play a significant role in the pathogenesis of cardiogenic shock or seem to be altered as a consequence of it.
Keywords: Factor XII; Kallikrein; Septicemia; Septic shock; Cardiogenic shock